Determinants of Work–Life Balance Among Muslim Women Educators in the Jabodetabek Area - Sari, Novita; Indra (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2025)
Muslim women workers in the education sector play a strategic role as educators of the nation's next generation and household managers, making the balance between professional and domestic responsibilities a crucial issue in human resource management. This study aims to analyze the factors influencing the work-life balance (WLB) of Muslim women workers in the Greater Jakarta area by examining five key variables: religiosity, support from Islamic organizations, family support, work-family role conflict, and job demands. This study used a quantitative approach with a survey design and purposive sampling technique with 150 married Muslim women respondents working in formal educational institutions. Data collection was conducted using a five-point Likert-scale closed-ended questionnaire, and data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results showed that religiosity and family support had a positive and significant effect on WLB, while work-family role conflict had a significant negative effect. Conversely, organizational support and job demands did not significantly influence WLB. These results indicate that Muslim women's work-life balance is more determined by the strength of religiosity and family support than by organizational factors or workload. The implications of this study emphasize the importance of strengthening religious values ​​and family social support in policies for managing the female workforce in the education sector.